The pyramid of corporate social responsibility model: empirical evidence from Malaysian stakeholder perspectives / Asyraf Wajdi Dusuki and Tengku Farrah Maimunah Tengku Mohd Yusof - Dusuki, Asyraf Wajdi (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
There has been an increasing interest on the corporate social responsibility (CSR) worldwide. Many CSR concepts have been proposed based on the premise that the business institutions are part of the society. A set of CSR concept as proposed by Carroll (1979; 1991) is utilized by this study. This concept which is known as the Pyramid of CSR suggests that CSR is basically presented by four dimensions, namely, economic, legal, ethical and philanthropic in their respective order of importance. This concept is widely tested in the literature and most of them are examined from the western countries’ perspectives. Despite the extensiveness of empirical research on CSR in the West, past research investigating CSR concepts Malaysian stakeholders remains scarce. Therefore, this study provides empirical evidence from Malaysian stakeholders’ perspectives on CSR concept proposed by Carroll (1979; 1991). The study surveys a sample of 457 respondents (45.7% usable response rate). The results show that Malaysian stakeholders ranked the four dimensions as economic, ethical, legal and philanthropic accordingly. The ranking of dimensions by the Malaysian stakeholder was slightly different from the idealized model suggesting cultural factor as contributing to the differences. The study also highlighted gender, race, and education level, working experience and religiosity factors that contribute to the differences in perception.